Modernization of the current cannabis legal framework and its potential economic gains - Samuša, Annija (Riga Graduate School of Law, 2017)
The main topic of the article is to observe the current regulatory policy of cannabis and the reasons why it should be reorganized so that the society could gain largest potential economic benefit. The author basically wanted to prove the need for changes in international cannabis regulation. In order to gain the best results, the author uses legal and comparative analysis research methods and as credible sources exploits mainly drug reports published by international organizations, scientific journal and official government data. The main findings are that the current international legislation regarding cannabis is outdated, ineffective and actually obstructs the society from researching the respective substance and its possible advantages. More liberal and at the same time more specific regulation of cannabis market is found to be more effective to defeat the black market and give benefit to society’s overall well-being. In the conclusion the author recommends to change the international cannabis legislation by presenting several step control mechanisms of the respective substance.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Drug policy; Marijuana; International drug legislation; Cannabis